The Role of Predictive Biomarkers, Clinical Features, and Chemoprevention Strategies in the Malignant Transformation of Oral Potentially Malignant Disorders to Oral Squamous Cell Carcinoma: A Meta-Analysis - Soomro , Azeem Hussain; Adnan, Romeysah; Iqbal , Tooba; Shah, Muniba; Anees , Mahrukh; Masud , Zahra; Ilyas , Urwa; Fatima , Dura; Shuaib , Ayesha (Indus Journal of Bioscience Research, 2025)
Background: Oral Potentially Malignant Disorders (OPMDs) pose a significant risk for progression into Oral Squamous Cell Carcinoma (OSCC), a leading cause of oral cancer-related mortality. Early detection and risk assessment are critical for timely intervention. This meta-analysis evaluates predictive biomarkers, clinical features, and chemoprevention strategies influencing the malignant transformation of OPMDs to OSCC. Methods: A systematic literature search was conducted across PubMed, Web of Science, Cochrane Library, and Scopus databases following PRISMA guidelines. Studies evaluating biomarkers, histopathological features, or chemopreventive treatments for OPMDs were included. Randomized controlled trials (RCTs), phase I and II clinical trials, and observational studies were analyzed. Statistical analysis, including heterogeneity assessment and bias evaluation, was performed using R software. Results: A total of 10 studies with 980 participants were included. PD-L1 expression, EGFR mutations, and histopathological dysplasia were identified as key predictive biomarkers, with PD-L1 showing a sensitivity of 80% and specificity of 75% for malignant transformation. Targeted therapies such as Nivolumab, Erlotinib, and chemopreventive agents, including Green Tea Extract and Vitamin A, demonstrated significant reductions in lesion progression. Smoking, betel quid use, and genetic mutations were strongly correlated with increased OSCC risk. Conclusions: This meta-analysis confirms that integrating predictive biomarkers with clinical risk assessment can enhance early detection and intervention for OPMDs at high risk of malignant transformation. Chemoprevention strategies show variable effectiveness, highlighting the need for individualized therapeutic approaches. Future research should focus on refining biomarker-based screening protocols and optimizing targeted chemoprevention to mitigate OSCC progression risk.